Disciplinary Power and Impression Management in the Trials of the Stansted 15. (June 2021) - Hayes, Graeme; Cammiss, Steven; Doherty, Brian
We bring Foucauldian and Goffmanian frameworks into dialogue to show how repressive and disciplinary power operate in the criminal trials of social movement activists. We do so through an ethnographic account of the trials on terrorism-related charges of a group of anti-deportation direct action protesters known as the Stansted 15, complemented by interviews with defendants. We argue that the prosecution of these activists on terrorism-related charges creates conditions of constraint which effectively serve to collapse the space for political and normative challenge, and obliges them to develop impression management strategies internalising and reproducing the court's expressive regime. We see these trials therefore as a normalising procedure whose goal is not the repressive application of custodial sentences, but rather a disciplinary disarming of radical critique so that leniency can be applied. At stake here, therefore, is the production through trial of the ideal disciplined liberal political subject.